Longitudinal Outcomes and Monitoring of Patients With Multisystem Inflammatory Syndrome in Children - Fremed, Michael A.; Farooqi, Kanwal M. (Frontiers in Pediatrics, 2022)
The acute manifestations and short-term outcomes of multisystem inflammatory syndrome (MIS-C) have been extensively described; however, our understanding of the longitudinal outcomes associated with this condition continue to evolve. Here we review the existing literature on outcomes of MIS-C up to 1 year following diagnosis and summarize current published expert recommendations for management and follow up of these patients.